Impact of Intra-Arterial Injection Parameters on Arterial, Capillary, and Venous Time-Concentration Curves in a Canine Model - Ahmed, A.S. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: Recent advances in flat panel detector angiographic equipment have provided the opportunity to obtain physiologic and anatomic information from angiographic examinations. To exploit this possibility, one must understand the factors that affect the bolus geometry of an intra-arterial injection of contrast medium. It was our purpose to examine these factors in a canine model. MATERIALS AND METHODS: Under an institutionally approved protocol conforming to Guide for the Care and Use of Laboratory Animals of the National Institutes of Health, 7 canines were placed under general anesthesia with isoflurane and propofol. Through a 5F catheter placed into the right common carotid artery, a series of biplane angiographic acquisitions was obtained to examine the effects caused by variation in the volume of injection, the rate of injection, the duration of injection, the concentration of contrast medium, and the catheter position on arterial, capillary, and venous opacification. The results of each injection protocol were determined from analysis of a time-contrast concentration curve derived from locations over an artery, in brain parenchyma, and over a vein. The curve was generated from 2D digital subtraction angiography acquisitions by using prototype software. The area under the curve, the amplitude of the curve, and the time to peak (TTP) were analyzed separately for each injection parameter. RESULTS: Changes in the injection protocols resulted in predictable changes in the time-concentration curves. The injection parameter that contributed most to maximum opacification was the volume of contrast medium injected. When the injection rate was fixed and the volume was varied, there was an increase in opacification (maximal) proportional to the injected volume. The injected volume also had an indirect (secondary) impact on the temporal characteristics of the opacification. The time-concentration curve became wider, and the peak was shifted to the right as the injection duration increased. The impact of injected volume on maximal opacification was significant (P < .0001), regardless of the site of measurement (artery, tissue, and vein); however, the impact on the temporal characteristics of the time-concentration curve reached statistical significance only in measurements made in the artery and the vein (P < .05), but not in the tissue (P > .1). The impact of injected volume on maximal opacification became nonproportional in the tissue and vein when the volume was very large (>12 mL). Increasing the concentration of contrast medium resulted in a nonproportional increase in the height of the time-concentration curves (P < .05). Injection rate had an impact on both maximal opacification and TTP. The impact on TTP occurred only when the injection rate was very slow (1 mL/s). Changes of concentration had a similar impact on the time-concentration curve. Catheter position did not cause significant alterations in the shape of the curves. CONCLUSIONS: There were predictable effects from modification of injection parameters on the contrast bolus geometry and on time-concentration curves as measured in an artery, brain parenchyma, or a vein. The amplitude, TTP, and area under the time-concentration curve depend mainly and proportionally on the amount of iodine traversing the vasculature per second. Other injection parameters were of less importance in defining bolus geometry. These findings mimic those observed in studies of parameters affecting bolus geometry following an intravenous injection.